Development and validation of UHPLC-MS/MS method for analysis of ziprasidone and its impurities - Čarapić, Marija; Marković, Bojan; Nikolić, Katarina; Agbaba, Danica (Archives of Pharmacy, 2022)
Ziprasidone, bensiothiasol piperazynylindolone derivative is second generation antipsychotic drug used for the treatment of schizophrenia and in acute maniac/mixed episodes associated with bipolar disorder. It has unique G-protein coupled receptor binding profile with relatively low propensity for weight gain. Recently, it became an official active pharmaceutical ingredient in European Pharmacopoeia, where there are three official chromatographic systems, one for the assay and two other for early-eluiting and late-eluting impurities. Therefore, the purpose of this investigation was to develop and validate a fast, highly sensitive UHPLC-MS/MS method for the analysis of ziprasidone and its five impurities, significantly differing in polarity and pKa. Separation was performed using Thermo ACCELA UHPLC system (Thermo Scientific, Waltham, MA, USA) equipped with triple quad Mass Spectrometer Thermo TSQ Quantum Access Max (Thermo Scientific, Waltham, MA, USA) with a heated electro-spray ionization interface. Satisfactory chromatographic separation was achieved using a gradient elution with mobile phase A (10mM ammonium formate buffer, pH 4.7) and mobile phase B (acetonitrile) on a Acquity UPLC BEH C18 (50×2.1 mm, 1.7 μm) column with mobile phase flow rate of 300 µL/min. Sample injection volume was 10 μL. The analysis runtime was 7 minutes. The method was validated according to the International Conference of Harmonization (ICH) guidelines and validation included parameters such as specificity, linearity, accuracy, precision, limit of quantification and limit of detection. The proposed rapid and sensitive method is convenient and reliable for the assay and purity control in raw materials and in dosage forms.